A study on EEG differences between active counting and focused breathing tasks for more sensitive detection of consciousness - You, Yimeng; Li, Yahui; Yu, Baobao; Ying, Ankai; Zhou, Huilin; Zuo, Guokun; Xu, Jialin (Frontiers in Neuroscience, 2024)
In studies on consciousness detection for patients with disorders of consciousness, difference comparison of EEG responses based on active and passive task modes is difficult to sensitively detect patients' consciousness, while a single potential analysis of EEG responses cannot comprehensively and accurately determine patients' consciousness status. Therefore, in this paper, we designed a new consciousness detection paradigm based on a multi-stage cognitive task that could induce a series of event-related potentials and ERD/ERS phenomena that reflect different consciousness contents. A simple and direct task of paying attention to breathing was designed, and a comprehensive evaluation of consciousness level was conducted using multi-feature joint analysis. Finally, we quantified the degree of differences in EEG response under different conditions using machine learning. EEG data from 20 healthy subjects were compared and analyzed. The results showed that the EEG responses of the subjects under different conditions were significantly different in the time domain and time-frequency domain. Compared with the passive mode, the amplitudes of the event-related potentials in the breathing mode were further reduced, and the theta-ERS and alpha-ERD phenomena in the frontal region were further weakened. There was a greater difference in EEG response between the breathing mode and the active mode. By analyzing multiple features of EEG responses in both modes simultaneously, a more sensitive and accurate consciousness detection is expected. This study can provide a new idea for traditional consciousness detection methods.